Avaliação da introdução de cal hidratada nas argamassas aplicadas sobre blocos cerâmicos e sua influência no desempenho e morfologia - Giuliano Polito (2008)
This work aims to investigate the bond strength of the finishing coat of mortar applied onto a ceramic block (brick) masonry, focusing on the analysis of the microstructure of the mortar/substrate interface, correlating to mechanical behavior of the mortar and the addition of hydrated lime in the mortar. Five distinct mortar types applied on the dry ceramic block substrate were assessed, using techniques for preparation and implementing, which are common at the construction site. The study was carried out using the scanning electron microscope with EDS microanalyzer (SEM-EDS), in order to identify the main hydration products present at the interface. Also, X-ray fluorescence spectrometry (XRF) was used to verify the depth of penetration of the hydration products, moreover analysis of characterization of the mortar in hard and plastic form. The results showed evidence that the main phase responsible for the bond strength between the plaster and the ceramic block is etringite. The adherence occurs by the interlocking of etringite crystals and their penetration within the pores of the substrate, which were observed inside these pores until a depth of 500µm. This penetration was confirmed by the variations in the concentrations of related chemical elements, depending on depth, by the XRF technique. It wasnt observed any direct relation between the calcium penetration depth and the bond strength. The depth and calcium penetration quantity is related to the binders quantity, inother words, ciment and/or lime. Different morphologies of the hydration products of the binders have been observed. The crystals formed at the interface are more euhedral and larger than the rest of the matrix and have a preferential orientation, perpendicular to the surface of the block. In this region, the presence of etringite is predominant and, in lower concentrations, there is also CSH (calcium silicate hydrate) and calcite. This is due to the increased mobility of sulfate, calcium and aluminum ions during the cement hydration and the proximity to the porous substrate, which provides the suction of the ions-bearing fluid to its interior. Different morphologies of the etringite crystals were also observed for the various mortar types used, probably caused by the variation of the contents of lime and binder in the mortar. The lime variation also influenced the mortar bond extension and thickness, in this way, affecting the strength values and rupture type (form). It was observed in the dig up tests that, after the rupture of the mortar, a thin later remains bonded to the brick, seen at naked eye, showing that the rupture happened due to the consistency lack of the mortar close to the interface, around 200µm far. This behavior makes clear that the rupture didnt occur along the range full of etringita, but within the mortar layer, near the contact surface.